Comparison of flexibility options to improve the value of variable power generation - Juha Kiviluoma; Erkka Rinne; Niina Helistö (International Journal of Sustainable Energy, 2018)
As the share of variable generation in power systems increases, there is increasing value in more flexible use and generation of electricity. The paper compares the economic value of several flexibility options in a large power system with a large amount of reservoir hydro power. Generation planning models are needed to consider the impact of flexibility options on other investments in a power system. However, generation planning models do not include all the relevant operational details. The approach in the paper combines a generation planning model with a unit commitment and dispatch model. The results demonstrate the value of coupling the heat and power sectors and the value of transmission. Low-cost electricity storage does not appear to be as decisive in the Northern European context with wind power as the main variable generation source. The paper also addresses methodological issues related to the inclusion of operational constraints in generation planning.